Relationship between exercise capacity and glucose tolerance in cystic fibrosis. Issue 2 (8th November 2017) - Foster, Karla; Huang, Guixia; Zhang, Nanhua; Crisalli, Joseph; Chini, Barbara; Amin, Raouf; Elder, Deborah
Abstract: Background: Improved exercise capacity (EC) and normal glucose tolerance (NGT) are independently associated with favorable outcomes in CF, however, little information on this relationship exists in patients with CF. Methods: Cardiopulmonary exercise tests, oral glucose tolerance tests (OGTT), and HbA1c values measured within a 12‐month period were evaluated on 83 pediatric patients diagnosed with CF. Patients were categorized as having NGT, abnormal glucose tolerance (AGT), or CF‐related diabetes (CFRD). Results: EC decreased as severity of glucose intolerance increased across NGT, AGT, and CFRD groups ( P = 0.02). Compared to patients with NGT, patients with CFRD had lower peak VO2 mL/kg/min (33.0 ± 7.3 vs 41.3 ± 9.4, P = 0.01), lower VO2 % (81 ± 20 vs 93 ± 17, P = 0.03), and higher HbA1c (6.9 ± 1.7 vs 5.4 ± 0.4, P < 0.01). There was a positive association with age and FEV1 % with EC in the 17 patients with CFRD. In the 66 patients without diabetes, peak EC was positively associated with FEV1 % and negatively associated with age, fasting insulin, and insulin 120 min. After accounting for age and FEV1 %, multivariate analyses indicated that insulin and glucose values at 120 min predicted EC. Conclusions: These data provide evidence that poor glucose tolerance is associated with lower EC in pediatric patients with CF. There was a significant relationship between glucose and insulin values obtained by OGTT with EC in a sample of non‐diabetic patients with preserved lung function. Future studies are warranted to confirm these findings and investigate the potential role of exercise in the management or prevention of CFRD.